Influence of overhead on processor allocation for multiple loops - Gubitoso, M. D. M.; Song, S. W. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 1995: Anais do VII Simpósio Brasileiro de Arquitetura de Computadores e Processamento de Alto DesempenhoDO - 10.5753/sbac-pad.1995.19876, 1995)
We consider two consecutive and independent forall loops and the strategy to allocate processors for their execution. One strategy is to execute each of the two loops consecutively, each time with all the available processors. Another strategy is to execute both loops simultaneously, each with a fraction of the available processors. We verify that the presence of overhead can influence this strategy, since the second strategy implies the use of a smaller number of processors for each individual loop, reducing thus the effect of the overhead. We establish conditions under which the second strategy is better. Finally we consider the special case when there is a single forall loop. We show conditions under which it is more advantageous to split it into two smaller loops and execute them simultaneously, each with a fraction of the available processors.